Quantitative trait loci mapping for conjugated linoleic acid, vaccenic acid and ∆9‐desaturase in Italian Brown Swiss dairy cattle using selective DNA pooling. (9th June 2014) - Strillacci, M. G.; Frigo, E.; Canavesi, F.; Ungar, Y.; Schiavini, F.; Zaniboni, L.; Reghenzani, L.; Cozzi, M. C.; Samoré, A. B.; Kashi, Y.; Shimoni, E.; Tal‐Stein, R.; et al.
Summary A selective DNA pooling approach was applied to identify QTL for conjugated linoleic acid (CLA), vaccenic acid (VA) and Δ9‐desaturase (D9D) milk content in Italian Brown Swiss dairy cattle. Milk samples from 60 animals with higher values (after correction for environmental factors) and 60 animals with lower values for each of these traits from each of five half‐sib families were pooled separately. The pools were genotyped using the Illumina BovineSNP50 BeadChip. Sire allele frequencies were compared between high and low tails at the sire and marker level for SNPs for which the sires were heterozygous. An r procedure was implemented to perform data analysis in a selective DNA pooling design. A correction for multiple tests was applied using the proportion of false positives among all test results. BTA 19 showed the largest number of markers in association with CLA. Associations between SNPs and the VA and Δ9‐desaturase traits were found on several chromosomes. A bioinformatics survey identified genes with an important role in pathways for milk fat and fatty acids metabolism within 1 Mb of SNP markers associated with fatty acids contents.